Simulation of Altered Excursion of the Pronator Quadratus - Feeney, Micheal S. (Thieme Medical Publishers, 2014)
Background Loss of forearm rotation is frequently seen after healing of distal radius fractures. Questions/Purposes Our purpose was to determine whether restricted excursion of the pronator quadratus muscle can affect forearm rotation. Methods We evaluated the relationship between pronator quadratus excursion and forearm rotation in a cadaveric model. Eight adult fresh-frozen above-elbow specimens were attached to a mounting device that permitted free rotation of the forearm around its ulnar axis. Forearm rotation was measured with a protractor while alternating pronation and supination loads were applied. Measurements were repeated after restricting the excursion of pronator quadratus by 10, 20, and 30% of its initial length. Results There was a mean 15° loss of supination for each 10% reduction in pronator excursion. There was no significant effect on pronation. Conclusions We conclude that, independent of any bone deformity or nearby joint stiffness, posttraumatic scarring of this muscle may result in a loss of supination.